Multiples Myelom und seine Vorstufen - Maatouk, Imad; Goldschmidt, Hartmut; Hillengaß, Jens (Der Onkologe, 2018)
BackgroundMultiple myeloma (MM) is a common malignant hematological disease with an incidence of about 7 new cases per 100,000 inhabitants. The disease remains incurable in the vast majority of patients. Against this background, recording physical and mental health-related quality of life is becoming increasingly important. Symptomatic MM is preceded by premalignant stages. Monoclonal gammopathy of undetermined significance (MGUS) can turn into MM with a prevalence of 1-3%/year. Smoldering MM (SMM) has an average probability of 10%/year to turn into symptomatic MM.ObjectivesThe findings on health-related quality of life and psychological stress in MM are reviewed and classified, and the mental stress (distress) in patients with MM and premalignant stages (MM/SMM) are compared.MethodsReview of the literature and evaluation of our own data.ResultsWhile there are some studies on the quality of life and psychological stress from MM, there are hardly any surveys of these aspects among patients with SMM or MGUS. Comparisons with regard to mental stress show (compared to MM) similarly high levels of stress in patients with MGUS and SMM.ConclusionsIn the future, further studies on health-related quality of life and psychological stress should be carried out in MGUS, SMM, and MM. In a further step, longitudinal investigations with repeated measurements could be performed in order to learn more about predictors and their progression and to be able to make corresponding offers of support.
Gesehen am 06.08.2019